Pengaruh Kebijakan Program Restrukturisasi terhadap Kinerja Perbankan pada Masa Pandemi Covid-19 di Indonesia - Dedy Sunaryo Nainggolan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The COVID-19 pandemic demonstrated the resilience and vulnerability of financial systems worldwide, including Indonesia’s banking sector. This unprecedented crisis required governments and financial authorities to adopt policies capable of supporting economic survival, limiting financial instability, and sustaining institutional growth. One key policy was credit restructuring, introduced to reduce economic pressure and prevent a sharp increase in non-performing loans. This study examines the implementation of POJK No. 11/POJK.03/2020 on National Economic Stimulus as an anti-imbalance policy for banking institutions during the pandemic. The research analyzes whether the restructuring program functioned effectively or merely served as a temporary precaution until economic conditions recovered. Using the CAMEL method, this study evaluates Indonesian banking statistics from January 2019 to December 2023. The findings indicate that credit restructuring helped maintain a strong Capital Adequacy Ratio and supported operational efficiency. Banking performance also generally showed consistent profitability during the pandemic, which contributed to sustainable capital strengthening and operational stability. Although non-performing loans remained below 3%, the analysis highlights the need for continued monitoring when NPL levels exceed 2%. Long-term policy success depends on effective early warning systems and the integration of restructuring into a risk-based macroprudential framework. Timely implementation can prevent broader systemic banking sector damage.